Analisis akuntabilitas kinerja instansi pemerintah pada Dinas Kesehatan Daerah Provinsi Sulawesi Utara - Tambajong, Indri Intan Yunike; Warongan , Jessy D. L.; Maradesa, Djeni (Riset Akuntansi dan Portofolio Investasi, 2024)
Government Agency Performance Accountability is a form an agency’s abligation to accoun for the success and failure of mission implementation in achieving set goals and objectives. This study aims to find out how accountability for the performances of government agencies in the Regional Health Office of North Sulawesi Province. This type of research is descriptive qualitative data analysis method used in this research is descriptive method. The results of this study indicate that performance accountability (starting from strategic planning to performance evaluation) of the Regional Health Office of North Sulawesi Province is in accordance with Presidential Regulation No. 29 of 2014. However, in terms of performance measurement, there are several indicators that were not achieved due to the Covid-19 pandemic in 2020-2021 which resulted in not implementing hospital accreditation and an increase in the number of maternal deaths. As well as there are abstacles that occur in performance reporting in the LAKIP preparation process, namely in terms of ability to prepare LAKIP and there are delays in data collection and in data processing the lack of ability of staff to use existing applications.